2001
DOI: 10.1002/mc.1053
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of imprinting of IGF2 and MEST in lung adenocarcinoma

Abstract: Genomic imprinting is a parental origin-specific chromosomal modification that causes differential expression of maternal and paternal alleles of a gene. Accumulating evidence suggests that deregulation of imprinted genes, including loss of imprinting (LOI), plays a role in oncogenesis. In the present study, we investigated allelic expression of six imprinted genes in human lung adenocarcinomas as well as in matched normal lung tissue. Informative cases showing heterozygosity for the gene of interest were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 46 publications
6
62
2
Order By: Relevance
“…Interestingly, we observed that LOI/LOH of H19DMR not only was associated with higher IGF2 levels, but significantly correlated with overexpression of MEST and NNAT, which play an important role in fetal development (20)(21)(22)(23). Similar findings were published by Kohda et al who described a correlation of LOI at the IGF2/H19 locus and the MEST locus in case of lung adenocarcinomas (23).…”
Section: ------------------------------------------------------------supporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, we observed that LOI/LOH of H19DMR not only was associated with higher IGF2 levels, but significantly correlated with overexpression of MEST and NNAT, which play an important role in fetal development (20)(21)(22)(23). Similar findings were published by Kohda et al who described a correlation of LOI at the IGF2/H19 locus and the MEST locus in case of lung adenocarcinomas (23).…”
Section: ------------------------------------------------------------supporting
confidence: 90%
“…Similar findings were published by Kohda et al who described a correlation of LOI at the IGF2/H19 locus and the MEST locus in case of lung adenocarcinomas (23). Thus, it might be …”
Section: ------------------------------------------------------------supporting
confidence: 88%
See 1 more Smart Citation
“…IGF2 expression is from the paternal allele, whereas the maternal allele is normally inactive. IGF2 imprinting is relaxed in many different types of tumors, including osteosarcoma (7), lung adenocarcinomas (8), head and neck squamous cell adenocarcinomas (9,10), Wilms' tumor (11), prostate cancer (12), and colorectal carcinomas (13)(14)(15)(16)(17). This loss of imprinting (LOI) occurs when there is abnormal activation of the maternal copy of IGF2 and the resultant overexpression contributes to tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous IGF-1 as a growth factor may also promote the growth of the tumor cells. IGF-1 combines with its receptors to activate the PI3K/Akt and MAPK signaling pathways (10), inhibiting tumor cell apoptosis and promoting cell proliferation, respectively (11)(12)(13)(14). In the present study, the results indicated that the growth of the transplanted colorectal tumor tissues from the mouse T2DM model was more rapid than that from the normal mice.…”
Section: Discussionmentioning
confidence: 61%